Enhancement of the Low Voltage Ride Through Capability for Doubly Fed Induction Generator During Grid Voltage Dip - Altabbakh, M. M.; Ergene, L. T. (IEEE, 2019)
In this paper an enhancement of Low Voltage Ride Through (LVRT) capability for grid connected Wind Turbine (WT) driven Doubly Fed Induction Generator (DFIG) when a severe balanced three phase voltage dip occurs is done by using crowbar protection circuit. A comparison between the behavior of DFIG with and without crowbar protection circuit during voltage dip is simulated. Stator flux oriented vector control method is applied on Rotor Side Converter (RSC) to control the generated active and reactive power separately, where a grid voltage oriented vector control is applied on Grid Side Converter (GSC) to control the reactive power and voltage in the DC-link. The DFIG with crowbar protection circuit model is built in Matlab. The simulation results show the effectiveness of using the crowbar protection circuit in reducing RSC currents three times less, and keeping the DC- link voltage close to its reference value during voltage dip.